PEMANFAATAN BUKU ASIP DAN PANDUAN IBU HAMIL, NIFAS DAN MENYUSUI DI MASA PANDEMI COVID-19 DI PUSKESMAS DEPOK II - Ratna Lestari Budiani Buana; Nia Fararid Askar; Lilis Rohani; Patria Bella Violentina; Ika Agustin Atika Putri (P3M Universitas Aisyiyah Surakarta, 2023)
COVID-19 pandemic become a global issue which affected various aspects especially health sector. Every health facility in Indonesia is conducted to focus on the COVID-19 cases, in consequent, the non COVID-19 matter is being disregarded such as maternal problem.Puskesmas Depok II, kabupaten Sleman, D.I. Yogyakarta is the objective of this society program due to Sleman has the highest number of cases among other district in D.I. Yogyakarta. This program collaborated with SEKOCI (Sekolah Komplementer Cinta Ibu) a group of mothers or future mothers in Puskesmas Depok II area.The program activity started by revising the Buku ASIP which written before by adding some information about health protocol for maternal in pandemic COVID-19. The new revision is collaborated with Puskesmas Depok II midwife. Dissemination by online and offline is done after the book is printed and ready to distribute to member of SEKOCI from Puskesmas Depok II and all over Indonesia. Moreover, an online survey is conducted to measure the book’s benefit.The survey result shows that Buku ASIP give enough information to the user especially in pandemic condition.